2007
DOI: 10.1111/j.1460-9568.2007.05785.x
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of conscious error recognition: aware and unaware errors in an antisaccade task

Abstract: Event-related potential (ERP) studies identified the error-related negativity (Ne/ERN) and the error positivity (Pe) to be associated with performance errors. However, the functional significance of these components is not yet resolved. With the present study we intended to further investigate to what extent these components are related to error awareness. ERPs were recorded during an antisaccade task, and error awareness was obtained from accuracy ratings on each trial. In accordance with earlier findings, aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
252
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(288 citation statements)
references
References 30 publications
27
252
8
1
Order By: Relevance
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Corrected errors were also associated with a significant positivity peaking at 113ms after the key-press. This post-ERN positivity is considered to be the early Pe (Endrass et al, 2007;O'Connell et al, 2007;van Veen & Carter, 2002) based on its tight temporal coupling to ERN, topography, onset and dipole location, rather than the late Pe which is a centro-parietal ERP component shown to be functionally dissociable from the ERN (see Endrass, Klawohn, Preuss, & Kathmann, 2012;Endrass et al, 2007). Uncorrected errors were associated with a brief but significant negativity compared to matched correct key-presses between 63ms and 55ms before the error.…”
Section: Behavioural Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies find similar neural correlated for reported and non-reported errors (Nieuwenhuis et al, 2001;Endrass et al, 2007Endrass et al, , 2012O'Connell et al, 2007;Shalgi et al, 2009;Hester et al, 2005Hester et al, , 2009Klein et al, 2007), whereas other studies find different neural correlates for aware and unaware errors (Steinhauser and Yeung, 2010;Wessel et al, 2011;Shalgi and Deouell, 2012). It must be considered, however, that most of these studies are limited to the cortical electrophysiology of error reactivity -behavioral adjustments have not been considered.…”
mentioning
confidence: 98%
“…Antisaccades require one to inhibit the prepotent response of looking toward a suddenly appearing stimulus and to look instead in the opposite direction. Antisaccade errors (i.e., looking toward the stimulus) reliably elicit both dACC activation (14,25) and the ERN (26)(27)(28)(29). We estimated the source of the ERN from the combined EEG and MEG data.…”
mentioning
confidence: 99%